Perancangan Sistem Informasi Penggajian Karyawan Pada Koperasi Syariah Islamic Centre Bekasi Berbasis Web - Rina Fitriani -; Marhakim Marhakim; Adhitya Ilham Ramdhani Ramdhani; Siti Arum (Jurnal ICT: Information Communication & Technology, 2022)
The Syariah Islamic Center Bekasi Cooperative is one of the cooperatives in Bekasi that organizes parking service management businesses, catering needs providers, financing units (Goods Credit), Retail (Ic Mart, Canteen, and Kedai Kopsyar) which still use Microsoft Word and Excel in making their reports. If an economic data processing activity is still done manually it will cause various problems, including requiring quite a long time just to make records, checking existing data one by one and the information conveyed to managers is always late. Therefore we need a computerized system, especially web-based with the waterfall method in order to provide information to employees and other parties quickly, precisely and accurately.